Control Method of Fabric Actuator Suit for Gaze Guidance in Immersive Spaces - Yokoe, Kenta; Aoyama, Tadayoshi; Funabora, Yuki; Nakagawa, Koki; Sakai, Yusuke; Takeuchi, Masaru; Hasegawa, Yasuhisa (Proceedings of the International Symposium on Micromechatronics and Human Science, 2022)
In recent years, there has been a growing demand for teleoperation in immersive spaces. Users wear a head-mounted display in the immersive spaces to obtain visual information from all directions. However, they often lose sight of the target object owing to the large amount of obtained visual information. Therefore, this study proposes a novel system to physically guide a user's gaze without using visual information by using a fabric actuator suit. A fitting algorithm is implemented in the proposed system for the fabric actuator suit along with a pressure control method for the actuator and subject experiments are conducted to verify the physical gaze guidance.